Physicochemical Compatibility and Stability of Linezolid with Parenteral Nutrition - Tomczak, Szymon (Molecules, 2019)
Patients referred to intensive care units (ICU) require special care due to their life-threatening condition, diseases and, frequently, malnutrition. Critically ill patients manifest a range of typical physiological changes caused by predominantly catabolic reactions in the body. It is necessary to provide the patients with proper nutrition, for example by administering total parenteral nutrition (TPN). The addition of linezolid to TPN mixtures for patients treated for linezolid-sensitive infections may reduce the extent of vascular access handling, resulting in a diminished risk of unwanted catheter-related infections. The compatibility and stability studies were conducted of linezolid in parenteral nutrition mixtures of basic, high- and low-electrolytic, high- and low-energetic and immunomodulatory composition. Mixtures containing linezolid were stored at 4–6 °C and 25 °C with light protection and at 25 °C without light protection for 168 h. In order to evaluate changes in the concentration of linezolid a previously validated reversed-phase HPLC method with UV detection was used. It was found that linezolid was stable at 4–6 °C in the whole course of the study whereas at 25 °C it proved stable over a period of 24 h required for administration of parenteral nutrition mixtures. The TPN mixtures demonstrated compatibility with linezolid and suitable stability, which were not affected by time or storage conditions.